Public-private partnership in medicine: international experience and Kazakhstan practice - Orynbasarov, S.O.; Urazbaeva, Z.O.; Orynbassarova , А.А. (BUKETOV BUSINESS REVIEW, 2023)
Object: Studying of the international experience of public-private partnerships in medicine is to understand how different countries have implemented these partnerships in the field of healthcare and what impact they have had on the provision and quality of medical services. Methods: PPP research includes both quantitative and qualitative methods for studying various aspects of cooperation between the state and the private sector, as well as comparative analysis. Findings: Public-private partnership in medical research refer to collaboration between publicly funded research institutions and the private sector to conduct medical research. This type of research can be useful for several reasons: it can help accelerate the development of new treatments and technologies, improve patient outcomes, and promote economic growth. Conclusions: One example of research in the field of medicine between the state and the private sector is the development of vaccines. Government-funded research institutions often conduct basic research on vaccines, while the private sector takes over the production and distribution of vaccines. This collaboration has led to the development of several highly effective vaccines, such as COVID-19 vaccines, which have played a crucial role in the global response to the pandemic. Government-funded research institutions can provide the scientific knowledge and resources needed to develop new medical technologies, while the private sector can share its manufacturing and marketing expertise to bring the technology to market. This collaboration has led to the development of many vital medical devices, such as pacemakers and artificial organs.